Scopus Indexing Delays of Articles Published in Major Pharmacy Practice Journals - Samuel Adeosun (INNOVATIONS in Pharmacy)
Background: Authors of bibliometric studies often wait for an arbitrarily prolonged period to allow for complete indexing of documents in the Scopus database after the end of the period to be studied (period-of-interest), thus negatively affecting recency (interval between publication date the date of the latest data reported) in bibliometric studies.